The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jbm.b.33404
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of pig and human‐derived aortic valve interstitial cells seeding on fixative‐free decellularized animal pericardium

Abstract: Glutaraldehyde-fixed pericardium of animal origin is the elective material for the fabrication of bio-prosthetic valves for surgical replacement of insufficient/stenotic cardiac valves. However, the pericardial tissue employed to this aim undergoes severe calcification due to chronic inflammation resulting from a non-complete immunological compatibility of the animal-derived pericardial tissue resulting from failure to remove animal-derived xeno-antigens. In the mid/long-term, this leads to structural deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 59 publications
4
34
0
Order By: Relevance
“…Valvular interstitial and endothelial cells were seeded in vitro gravimetrically. SEM of the surface of the pericardial tissue and the cell viability assay have helped to demonstrate that the tissue utilized was a suitable substrate for both cell types as cell seeding occurred matching the results of other studies (Figure S1; Santoro et al, ). Lanuti et al () was able to show re‐endothelialization of a heart valve scaffold, and likewise, in this study, endothelial cells were colonized on the surface of the tissue.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Valvular interstitial and endothelial cells were seeded in vitro gravimetrically. SEM of the surface of the pericardial tissue and the cell viability assay have helped to demonstrate that the tissue utilized was a suitable substrate for both cell types as cell seeding occurred matching the results of other studies (Figure S1; Santoro et al, ). Lanuti et al () was able to show re‐endothelialization of a heart valve scaffold, and likewise, in this study, endothelial cells were colonized on the surface of the tissue.…”
Section: Discussionsupporting
confidence: 78%
“…Overall, decellularization and sterilization trends towards shifting the mechanical properties, from UTS to stiffness, to more closely resemble the mechanical properties of a native porcine valve(Figure 1), which could potentially allow this material to be superior to current dogmas in terms of cellular favorability.Valvular interstitial and endothelial cells were seeded in vitro gravimetrically. SEM of the surface of the pericardial tissue and the cell viability assay have helped to demonstrate that the tissue utilized was a suitable substrate for both cell types as cell seeding occurred matching the results of other studies (Figure S1;Santoro et al, 2016) Lanuti et al (2015). was able to show reendothelialization of a heart valve scaffold, and likewise, in this study, endothelial cells were colonized on the surface of the tissue.…”
supporting
confidence: 87%
“…Two different decellularization procedures were used and compared. The first, named SDS , was previously described by us (Santoro et al, ), and the second, named Triton , is a refinement of this protocol. Briefly, both procedures started with a mechanical removal of fat tissues, followed by three 30‐min washings in Ca 2+ ‐ and Mg 2+ ‐free phosphate‐buffered saline (PBS) containing protease inhibitors (aprotinin, 10 KIU/ml, Trasylol, Bayer, Germany) under continuous agitation.…”
Section: Methodsmentioning
confidence: 99%
“…The decellularization procedure was also shown not to alter the three‐dimensional structure and the composition of the extracellular matrix, as well as the tissue mechanical behaviour. When the method was tested to assess the compatibility of the animal‐derived pericardium for tissue engineering applications (Santoro et al, ), we found complete removal of animal xenoantigens and the lack of toxic residuals that could impair growing of aortic‐valve‐derived interstitial cells, the cell type naturally deputed to valve tissue homeostasis and matrix renewal (A. C. Liu, Joag, & Gotlieb, ; Taylor, Batten, Brand, Thomas, & Yacoub, ). On the basis of these results, in the present contribution, we employed a direct perfusion bioreactor to achieve an efficient and homogeneous delivery of valve interstitial cells (VICs) into the decellularized pericardium (Cioffi et al, ; Wendt, Marsano, Jakob, Heberer, & Martin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The glutaraldehyde-fixed pericardium is the choice for bioprosthetic valve preparation, but this method may be accompanied by calcification caused by the lack of complete biocompatibility in human bodies in some preparation methods [67,68]. Santoro et al [69] found that the fixative-free decellularization of BP seeded with the interstitial cells of the aortic valve could be a more immunocompatible tissue and be used to develop tissue-engineered heart valves with seeded cells. Kajbafzadeh et al [25] demonstrated that tissue-engineered sheep pericardium seeded with autologous bladder smooth muscle cells might improve the efficacy of the pericardium in the regeneration of the bladder wall.…”
Section: Pericardial Tissue Features and Feasibilitymentioning
confidence: 99%